Status review of challenge, constraints and needs of men, women, and youth enterprises in the bean value chain in selected countries - Lutomia, Cosmas Kweyu; Nchanji, Eileen Bogweh (2022)
Common bean is the most grown legume in sub-Saharan Africa and contributes to income and food security of smallholder farmers. The common bean value chain offers business opportunities to various actors, particularly women because of their high involvement in production and marketing. The value chain has the potential to contribute to SDGs if opportunities are harnessed through developing and supporting SMEs and entrepreneurs. Nonetheless, challenges and constraints undermine the contribution of the common bean to livelihoods and incomes of actors along the chain. Key challenges are low use of improved seed, weak market linkages, lack of machinery and equipment, limited access to credit by value chain actors, context-specific barriers that undermine women and youth involvement, and lack of storage facilities. These challenges highlight needs for men, women, and youth entrepreneurs. The Improving Bean Production and Marketing in Africa (IBPMA) project responded to the challenges faced by farmers and entrepreneurs in common bean value chain in 31 countries in sub-Saharan Africa through innovative programs. PABRA used the corridor approach to implement the project. This desk review was conducted to identify needs of men, women, and youth enterprises in bean value chain in countries targeted by the IBPMA project. Specifically, the report aimed to: • Identify types of challenges and constraints experienced at different stages of the common bean value chain in six selected countries in the nine PABRA bean corridors. • Better understand gender differences in challenges experienced by entrepreneurs at different stages of the common bean value chain. • To identify areas of need for men and women entrepreneurs that are central to improving the performance and sustainable growth of bean enterprises. The review reveals challenges and constraints experienced by men, women, and youth entrepreneurs and SMEs across bean corridors. Financial, technical, capacity, technological and context-specific challenges impede performance and growth of entrepreneurs and SMEs. There is need for interventions in these areas to support SMEs and individual entrepreneurs and strengthen competitiveness of bean value chains.